Understanding identity development in context: comparing reflective and situated approaches to identity - Van Der Gaag, Mandy A. E.; Gmelin, J. Ole H.; De Ruiter, Naomi M. P. (Frontiers in Psychology, 2025)
Many recent approaches to identity share a foundational similarity with ecological psychology, namely, to place identity in its context. That is, they explicitly place identity in its physical and social environments. Yet, we can distinguish at least two different approaches that diverge fundamentally with regards to the role that this “context” has in identity. We refer to these approaches as “reflective identity” and “situated identity” approaches. While the reflective-identity approach views context and individual as separate entities with a bi-directional relationship, the situated-identity approach views context and individual as inherently intertwined and inseparable. While these approaches have emerged as independent from each other, we see potential for these two approaches to become comprehensively coordinated. To set the stage for such a coordination in future research, we provide a short overview of these different approaches to identity and describe where they align and diverge with regards to viewing identity as contextualized. After providing an overview of the key differences and similarities, we outline a possibility for integration and offer ideas for future lines of research that we see as fruitful for developing a comprehensive and coordinated approach to identity that takes context seriously.